Usulan Perbaikan Kualitas Layanan Maskapai Penerbangan X Menggunakan Integrasi QFD dan Model Kano - Prawira, Dede Jatmika; Iqbal, Muhamad; Kurniawati, Amelia (Jurnal Teknik Industri, 2012)
X Airlines is experiencing quality improvement issue related to complaints addressed to their service. Complaints are increasing in holiday and feast day, especially on January, August, September, and October. Improvement is needed to produce better service and better sevice is one of the key aspect of customer satisfaction. Customer satisfaction of X Airlines was measured based on several attributes. The service quality attributes were also grouped into must be, one dimensional, attractive, indifferent, questionable, and reverse category. The quality improvement was designed by using Quality Function Deployment (QFD) method and Kano Model. The result showed that customer’s satisfaction in all service quality attributes were still not being met the requrement. The key attribute indentified on satisfaction measurement and the Kano Category were the on time of departure corresponding to the schedule (one dimensional category), the efficient language storage facilities (one dimensional category), the tasty and good quality of the food (one dimensional category), and skilled staffs in serving the customer avoid tardiness, giving compensation when tardiness happened, conducting airlines staff service excellence program, conducting cooking class program, and providing high technology and up to date entertainment facilities on the plane.